Combined use of irinotecan with histone deacetylase inhibitor belinostat could cause severe toxicity by inhibiting SN-38 glucuronidation via UGT1A1 - Wang, L.; Chan, C.; Wong, A.; Wong, F.; Lim, S.; Chinnathambi, A.; Alharbi, S.; Lee, L.; Soo, R.; Yong, W.; Lee, S.; Ho, P.; et al. (Impact Journals LLC, 2017)
© Lingzhi Wang et al. SN-38, the active metabolite of irinotecan, and histone deacetylase inhibitors (HDACis) such as belinostat, vorinostat and panobinostat, have all been shown to be deactivated by glucuronidation via UGTs. Since they all compete for UGTs for deactivation, we aimed to investigate the inhibitory effect of various HDACis on the glucuronidation of SN-38. This inhibitory effect was determined by measuring the formation rate of SN-38 glucuronide after SN-38 incubation with human recombinant UGT1A isoforms (1A1, 1A6, 1A7 and 1A9) and pooled human liver microsomes (HLM, wild type, UGT1A1*1*28 and UGT1A1*28*28 allelic variants), with and without HDACis. The data showed that belinostat at 100 and 200 µmol/L inhibited SN-38 glucuronidation via UGT1A1 in a dose-dependent manner, causing significant decrease in Vmaxand CLint(p < 0.05) from 12.60 to 1.95 pmol/min/mg and 21.59 to 4.20 µL/min/mg protein respectively. Similarly, in HLMs, Vmaxdropped from 41.13 to 10.54, 24.96 to 3.77 and 6.23 to 3.30 pmol/min/mg, and CLintreduced from 81.25 to 26.11, 29.22 to 6.10 and 5.40 to 1.34 µL/min/mg protein for the respective wild type, heterozygous and homozygous variants. Interestingly, belinostat at 200 µmol/L that is roughly equivalent to the average Cmax, 183 µmol/L of belinostat at a dose of 1,400 mg/m2given intravenously once per day on days 1 to 5 every 3 weeks, was able to inhibit both heterozygous and homozygous variants to same extents (~64%). This highlights the potential clinical significance, as a large proportion of patients could be at risk of developing severe toxicity if irinotecan is co-administered with belinostat.